2020
DOI: 10.1186/s12902-019-0468-y
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining evidence base for the development of Feel4Diabetes intervention to prevent type 2 diabetes – a narrative literature review

Abstract: Background: Feel4Diabetes was a school and community based intervention aiming to promote healthy lifestyle and tackle obesity for the prevention of type 2 diabetes among families in 6 European countries. We conducted this literature review in order to guide the development of evidence-based implementation of the Feel4Diabetes intervention. We focused on type 2 diabetes prevention strategies, including all the phases from risk identification to implementation and maintenance. Special focus was given to prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 85 publications
0
9
1
1
Order By: Relevance
“…A különféle sportok jól kombinálhatók, és az életkorral ezek prioritása, gyakorisága változtatható. A családon kívül fontos minta az iskola és a lakóközösség is, amelyek prevenciós tevékenységeit koor dinálni szükséges [50]. Partnerséget kell kialakítani a kormányzati szervekkel, a helyi szervezetekkel, akár a hitélet szervezőivel, hogy mindenki több fizikai aktivitást végezzen.…”
Section: A Fizikai Aktivitás Jelentőségeunclassified
“…A különféle sportok jól kombinálhatók, és az életkorral ezek prioritása, gyakorisága változtatható. A családon kívül fontos minta az iskola és a lakóközösség is, amelyek prevenciós tevékenységeit koor dinálni szükséges [50]. Partnerséget kell kialakítani a kormányzati szervekkel, a helyi szervezetekkel, akár a hitélet szervezőivel, hogy mindenki több fizikai aktivitást végezzen.…”
Section: A Fizikai Aktivitás Jelentőségeunclassified
“…The design of the Feel4Diabetes intervention was based on the PRECEDE-PROCEED and the HAPA models, which led to the identification of the lifestyle behaviors that are associated with the risk factors to develop T2D in vulnerable population groups, as well as their determinants, which were the targets of the implemented intervention [7,8].…”
Section: Designmentioning
confidence: 99%
“…Previous randomized controlled trials (RCTs) have shown lifestyle interventions to be effective in improving lifestyle behaviors in individuals at high risk of developing T2D [7]. Still, given the nature of these interventions, including their intensity (frequent counseling sessions), duration (3-10 years), high demands in infrastructure and health professionals' skills and opportunistic screening procedures (i.e., recruitment of high-risk individuals via hospitals, door-to-door procedures or by providing incentives to possible participants), they cannot be scaled up and applied to the whole population in real-life conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, these strategies may be sub-optimal and do not rely on a complete understanding of the detailed cardiometabolic profiles of the general population 5 . Most of the screening and prevention strategies are simply based on a few factors such as age, body mass index, metabolic syndrome, hyperglycemia or risk score such as Findrisc 6 to identify eligible people. We tend to omit a potentially high variability in individuals at a given level of risk, for instance in terms of genetic profiles 7 , inflammation, oxidative stress 8 , insulin resistance 9 and hepatic gluconeogenesis 10 , that could open a window of opportunity for more relevant strategies.…”
Section: Introductionmentioning
confidence: 99%